2005
DOI: 10.1038/sj.bdj.4812653
|View full text |Cite
|
Sign up to set email alerts
|

Third molar treatment outcome: a comparison of patients' preferences in Sweden and Wales

Abstract: A Ai im m To elucidate and compare patients' outcome preferences for removal and retention of mandibular third molars in Sweden and Wales. S Su ub bj je ec ct ts s a an nd d m me et th ho od d The subjects comprised patients referred and scheduled for removal of one or both mandibular third molars in Sweden and Wales. The multi-attribute utility (MAU) methodology was applied to study patients' preferences for outcomes of removal and retention of the mandibular third molar. R Re es su ul lt ts s Relative weight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…A study that compared patients' outcome preferences for removal and retention of mandibular third molars in Sweden and Wales found that the outcomes of surgery were considered worse after third molar removal than retention. 17 In another study where patients had a third molar removed, more patients found that the effect on intake and enjoyment of food was a more adverse event than pain following surgery. 18 In the distally impacted lower third molar issue we must remember that there is a chance that some impacted lower third molars which are mesially or vertically impacted will change their position to a disto-angular position.…”
Section: Discussionmentioning
confidence: 99%
“…A study that compared patients' outcome preferences for removal and retention of mandibular third molars in Sweden and Wales found that the outcomes of surgery were considered worse after third molar removal than retention. 17 In another study where patients had a third molar removed, more patients found that the effect on intake and enjoyment of food was a more adverse event than pain following surgery. 18 In the distally impacted lower third molar issue we must remember that there is a chance that some impacted lower third molars which are mesially or vertically impacted will change their position to a disto-angular position.…”
Section: Discussionmentioning
confidence: 99%
“…Of these, 34 papers were considered for inclusion after stage 1. As shown in Figure 2, eight studies 17,20,[71][72][73][74][75][76] were initially included at stage 2. However, on further inspection, five [71][72][73][74][75] of the eight studies did not include information that was relevant to the population of interest; these papers were, therefore, subsequently excluded from the review.…”
Section: Quantity Of Included Evidencementioning
confidence: 99%
“…As shown in Figure 2, eight studies 17,20,[71][72][73][74][75][76] were initially included at stage 2. However, on further inspection, five [71][72][73][74][75] of the eight studies did not include information that was relevant to the population of interest; these papers were, therefore, subsequently excluded from the review. Bibliographic details and summary data from these five studies [71][72][73][74][75] are available in Appendix 2.…”
Section: Quantity Of Included Evidencementioning
confidence: 99%
See 1 more Smart Citation